Descriptions of two new species of Afrotropical Psychodidae (Diptera) - Ježek, Jan; Oboňa, Jozef (Zootaxa, 2016)
Two new species of moth flies (Diptera: Psychodidae: Psychodinae) are described and illustrated on the basis of male morphological characters. Neoarisemus nyahururuensis sp. nov. was collected in the vicinity of Thomson's Falls (Nyahururu) in Kenya and Tonnoiriella veronikae sp. nov. in Toamasina province, Madagascar, Analamazaotra 1.4 km SSW Andasibe vill. (Périnet).